CD27+CD38hi B Cell Frequency During Remission Predicts Relapsing Disease in Granulomatosis With Polyangiitis Patients - von Borstel, Anouk; Land, Judith; Abdulahad, Wayel H.; Rutgers, Abraham; Stegeman, Coen A.; Diepstra, Arjan; Heeringa, Peter; Sanders, Jan Stephan (Frontiers in Immunology, 2019)
Background: Granulomatosis with polyangiitis (GPA) patients are prone to disease relapses. We aimed to determine whether GPA patients at risk for relapse can be identified by differences in B cell subset frequencies. Methods: Eighty-five GPA patients were monitored for a median period of 3.1 years (range: 0.1–6.3). Circulating B cell subset frequencies were analyzed by flow cytometry determining the expression of CD19, CD38, and CD27. B cell subset frequencies at the time of inclusion of future-relapsing (F-R) and non-relapsing (N-R) patients were compared and related to relapse-free survival. Additionally, CD27+CD38hi B cells were assessed in urine and kidney biopsies from active anti-neutrophil cytoplasmic autoantibody-associated vasculitides (AAV) patients with renal involvement. Results: Within 1.6 years, 30% of patients experienced a relapse. The CD27+CD38hi B cell frequency at the time of inclusion was increased in F-R (median: 2.39%) compared to N-R patients (median: 1.03%; p = 0.0025) and a trend was found compared with the HCs (median: 1.33%; p = 0.08). This increased CD27+CD38hi B cell frequency at inclusion was correlated to decreased relapse-free survival in GPA patients. In addition, 74.7% of patients with an increased CD27+CD38hi B cell frequency (≥2.39%) relapsed during follow-up compared to 19.7% of patients with a CD27+CD38hi B cell frequency of <2.39%. No correlations were found between CD27+CD38hi B cells and ANCA levels. CD27+CD38hi B cell frequencies were increased in urine compared to the circulation, and were also detected in kidney biopsies, which may indicate CD27+CD38hi B cell migration during active disease. Conclusions: Our data suggests that having an increased frequency of circulating CD27+CD38hi B cells during remission is related to a higher relapse risk in GPA patients, and therefore might be a potential marker to identify those GPA patients at risk for relapse.